Pemahaman Moderasi Beragama dan Sikap Intoleransi Sosial : Understanding of Religious Moderation and Attitudes of Social Intolerance - Nisar; Mahyuddin; Muhammad Ismail (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2023)
Issue religious intolerance is one of the challenges in the life of Indonesian society today which is based on diversity both in terms of religion, race, culture, language. Of course there are differences in perspectives. Moreover, as a student who is equipped with knowledge, of course, he has critical power to convey a perception or view to others. Students are expected to be a strategic tool to internalize the values ​​of religious moderation in building tolerance. This study discusses the understanding of religious moderation and students' attitudes towards intolerance. This study uses descriptive qualitative research, namely research that describes the results of interviews in the field. Researchers took data with the method of observation, interviews, and documentation. The theory used is the theory of religious pluralism in which the understanding being taught that all religions have relative truth. Meanwhile, multiculturalism theory provides an understanding of cultural, ethnic and religious diversity. The results of this study indicate that students of the sociology of religion have understood religious moderation within the scope of the campus and within the community. They generally reject all forms of social intolerance that harm individuals or groups in the name of religion. This research can serve as a comparison to the phenomena and issues of intolerance in Islamic religious universities today.